Influences of Illness Perception on Medication Adherence in Muslim Patients with Myocardial Infarction after Percutaneous Coronary Intervention - Maramoh, Rusna; Kritpracha, Jaruwan; Chinnawong, Tippamas (Nursing Journal of The Ministry of Public Health, 2025)
Medication adherence after percutaneous coronary intervention (PCI) is crucial for effectively treating myocardial infarction. This predictive study aimed to examine the levels and influence of illness perception on medication adherence in Muslim patients with myocardial infarction after percutaneous coronary intervention. The sample group consisted of 60 Muslim patients with myocardial infarction after percutaneous coronary intervention at the outpatient department of Yala Hospital. The samples were selected using purposive sampling. The data were collected from January to March 2024. Questionnaires on illness perception and medication adherence were used, with reliability coefficients of .80 and .81, respectively. Data were analyzed using descriptive statistics and multiple regression analysis. The results indicated that the overall mean score for medication adherence was high (mean=3.72, SD=.21). Illness perception related to treatment or symptom control was found to predict 20% of medication adherence (R²adj=.20) in Muslim patients with myocardial infarction following coronary angioplasty. Therefore, healthcare providers can utilize patients’ perceptions of treatment and symptom control to develop programs aimed at promoting medication adherence in patients with myocardial infarction after coronary angioplasty effectively.